Impact of the National Professional Qualification Program (PNQ) on Income: An Econometric Analysis in Piracicaba/SP-Brazil - Ferraz, Diogo; Oliveira, Fabíola Cristina Ribeiro de (Pesquisa & Debate Revista do Programa de Estudos Pós-Graduados em Economia Política, 2017)
This paper presents the analysis of the results of the National Program for Professional Qualification - PNQ in Piracicaba/Sao Paulo - Brazil. It analyzed the impact of PNQ on the income of workers. The Theory of Human Capital is presented as a suitable theoretical basis. We used econometric method "diffs-in-diffs", which compares the income of a group of skilled workers with others who did not attend the program. It proved to be rise in income and increased formalization of skilled workers. It was proved the viability of public policy professional qualifications in the municipality.